DENTAL DISEASE IN CHILDREN DIAGNOSED WITH LIFE-LIMITING DISEASES. RETROSPECTIVE STUDY - Mihaela Hizanu; Elena Roxana Bogdan Goroftei; Florina Popa; Mădălina Duceac; Constantin Marcu; Mădălina Irina Ciuhodaru; Daniela Druguș; Letiția Doina Duceac (Romanian Society of Oral Rehabilitation, 2023)
Children diagnosed with life-limiting or life-threatening diseases are at risk of complex, chronic, multisystemic illnesses due to immune system deficiencies and significant organ fragility. There is little research on the dental care of children with such serious pathology, where oral and general health is compromised. Our study aims to investigate the impact of terminal illnesses on oral health, identifying oral and dental deficiencies present in a group of 35 children diagnosed with life-limiting diseases, between 2015-2022, in the palliative care services at the Palliative Care Center for Children - Lumina Association Bacau, Romania. Material and method: The study consists of retrospective analysis of data from medical records of children diagnosed with life-threatening illnesses. Results: The 35 children included in the study provided us with essential information about the types of dental conditions they face and the role of the dentist qualified for palliative care as an integral part of medical management. Against the backdrop of immunosuppression, the main odontogenic conditions encountered in the children in the study group were: Dental caries, gingival inflammation or bleeding, recurrent fungal and viral infections, malocclusion or dental alignment deficiencies; edentulism, dysfunctional tooth development, oral hygiene deficiencies, nutritional deficiencies, dysphagia, xerostomia, facial aesthetic deficiencies and compromised speech ability, all of which deteriorate quality of life and put it at risk. Conclusions: Pediatric patients diagnosed with life-limiting diseases are prone to premature loss of oral health through severe odontogenic dysfunction. The palliative care dentist must identify, assess and alleviate these difficulties through specific actions designed to alleviate symptoms and minimise pain and suffering. Psychological counselling must precede any medical, therapeutic and palliative care act.